Kinds Of Language Problems Of Kindergarten Children In Surakarta - Arif Siswanto; Hafidz Triantoro Aji Pratomo; Muryanti Muryanti; Windiarti Dwi Purnaningrum (Poltekkes Kemenkes Surakarta, 2021)
Background: Language and communication skills are essential skills that preschoolers must have. This ability is a precursor to further literacy skills which will later be useful in the academic process of children, so it is necessary to trace the language and communication skills of preschool children. Methods: This research is a survey research by distributing questionnaires to respondents. The questionnaire contains the profile of language and communication skills through parent reports. The analysis used is using descriptive statistics. Results: This study provides an overview of language and communication skills in depth. The language component consists of receptive language skills, expressive language skills, and initial literacy skills. Meanwhile, communication skills consist of attention and listening, the ability to follow simple commands, the ability to ask questions, and the ability to speak. About 20% of preschoolers have language skills below their peers. Conclusion: Data found on language skills of children under their peers. Further research is needed to prove broader data about preschool language skills.